TECHNIQUES FOR HUMAN IDENTIFICATION THROUGH DENTAL ARCHES: APPLICATIONS IN FORENSIC ODONTOLOGY - Lopez, Andres Santiago Quizhpi; de Oliveira, Luiz Eduardo Prestes; de Souza, Geovanna Maria Ramos Porto; Alves, Amanda Cypriano (Seven Editora, 2026)
Human identification through dental arches is an essential method in forensic dentistry, especially in cases of severe soft tissue degradation. This narrative review analyzes recent scientific evidence on the transition from analog methods to three-dimensional (3D) imaging technologies in the forensic setting. The study highlights the importance of comparing antemortem (AM) and post-mortem (PM) records, now enhanced by intraorbital scanners and automated segmentation algorithms, such as the "grid-cutting" method, which eliminates interference from gingival tissues in digital models. Additionally, microstructural markers, such as root cementum thickness for age estimation, and salivary antigen analysis for biological profile determination are discussed. It concludes that the implementation of digital workflows and the use of open-source software increase the accuracy and speed of forensic examinations, consolidating forensic dentistry as an indispensable technological tool in criminal investigations and mass disasters. DOI: https://doi.org/10.56238/sevened2026.003-006